2007
DOI: 10.1007/bf03031880
|View full text |Cite
|
Sign up to set email alerts
|

The forecast accuracy of Australian Bureau of Statistics national population projections

Abstract: This paper examines the forecast accuracy of Australian Bureau of Statistics national population projections produced from the 1960s to the early 2000s. As well as total populations, the accuracy of the following is assessed: age-sexspecific populations, the Total Fertility Rate, life expectancy at birth and net international migration. It is shown that forecasts of the 1960s and 70s were the most inaccurate; forecasts of the 1980s and later proved to be much more reliable. The paper goes on to take an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 17 publications
2
43
0
2
Order By: Relevance
“…Mortality forecasts based on subjective expert opinion are often biased by opinions about biological upper limits on human life span, and as a result, future improvements in mortality are capped (Olshansky, 1988). Mortality levels projected in this way have often turned out to be overstated, and population numbers underestimated, because mortality improved more than was foreseen or believed possible, particularly at older ages (Keilman, 1997;Lee & Carter, 1992;Murphy, 1995;Olshansky, 1988;Wilson, 2007). The existence of a fixed biological limit on the human life span, and its likely level, continues to be a subject of debate and disagreement among biologists, demographers and actuaries (Fries, 1980;Oeppen & Vaupel, 2002;Olshansky, 1988;Vaupel, 2001).…”
Section: Expectation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mortality forecasts based on subjective expert opinion are often biased by opinions about biological upper limits on human life span, and as a result, future improvements in mortality are capped (Olshansky, 1988). Mortality levels projected in this way have often turned out to be overstated, and population numbers underestimated, because mortality improved more than was foreseen or believed possible, particularly at older ages (Keilman, 1997;Lee & Carter, 1992;Murphy, 1995;Olshansky, 1988;Wilson, 2007). The existence of a fixed biological limit on the human life span, and its likely level, continues to be a subject of debate and disagreement among biologists, demographers and actuaries (Fries, 1980;Oeppen & Vaupel, 2002;Olshansky, 1988;Vaupel, 2001).…”
Section: Expectation Methodsmentioning
confidence: 99%
“…Wilson (2007) found that mean absolute errors of age-sex population projections for Australia were largest at the youngest and oldest ages, with high errors at older ages attributed to both inaccurate mortality rate forecasts and numbers by cohort moving into these age groups. Furthermore, official national and state projections are only provided for single ages to 99 and 84 and in aggregate for ages 100+ and 85+ respectively.…”
Section: Projected Very Elderly Population Numbersmentioning
confidence: 99%
See 3 more Smart Citations